Pengaruh Budaya Organisasi terhadap Innovative Behavior Melalui Komitmen Organisasi pada Dinas Perhubungan Provinsi Sumatera Utara - Setiawan, Teguh; Ardani, Hafiza Dila; Ritonga, Ilham Mubaraq (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the influence of organizational culture on innovative behavior through organizational commitment as an intervening variable in the North Sumatra Province Transportation Service. Path analysis is used in research design to determine the direction of the variables studied and show how significant the influence of the independent variable is on the dependent, either directly or indirectly through mediating variables. This research uses quantitative methods. In this study the entire population was the sample consisting of 138 employees at the North Sumatra Province Transportation Service. To collect data, this was done through questionnaires distributed to respondents. The data obtained was then processed using SPSS version 25 tools. The results of this research show that organizational culture has a positive and insignificant effect on innovative behavior, organizational culture has an indirect effect on innovative behavior which can be mediated by organizational commitment. Keywords: Organizational Culture, Innovative Behavior, Organizational Commitment.